2019
DOI: 10.15666/aeer/1702_24372447
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Wood Vinegar on Some Soil Microorganisms

Abstract: This study was carried out in order to determine the enzyme activity of the wood vinegar obtained from the hazelnut shells with the potential of bio-pesticide in agro-ecosystem soil, and its effect on the microfungi and heterotrophic bacteria in total. The study was realized in the production seasons of 2014-2015 and 2015-2016, in the ecological conditions of the province Muş (in Turkey) on winter wheat field and with four repetitions according to Randomized Blocks Experimental Design. The treatments within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…However, in a recent study, Goethen de Lima et al [69] found that wood vinegar may be toxic to Daphnia magna (microcrustacea), while no genotoxicity was detected for Allium cepae. Koc [26] reported that wood vinegar used at different doses to protect plants and/or crops in wheat agro-ecosystems did not have a negative effect on microbial factors determined in the soil. Steiner et al observed that the application of wood vinegar to Amazonian soils increased the metabolism of soil microorganisms by increasing microbial biomass, population growth and the microbe's efficiency [36].…”
Section: Spray Testmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent study, Goethen de Lima et al [69] found that wood vinegar may be toxic to Daphnia magna (microcrustacea), while no genotoxicity was detected for Allium cepae. Koc [26] reported that wood vinegar used at different doses to protect plants and/or crops in wheat agro-ecosystems did not have a negative effect on microbial factors determined in the soil. Steiner et al observed that the application of wood vinegar to Amazonian soils increased the metabolism of soil microorganisms by increasing microbial biomass, population growth and the microbe's efficiency [36].…”
Section: Spray Testmentioning
confidence: 99%
“…Wood vinegar obtained from biomass pyrolysis has applications in various areas, such as its use as a food additive, anti-inflammatory agent, anti-fungal drug or pest control agent [23] owing to its powerful antioxidant and antimicrobial activity [24][25][26][27][28]. There is also evidence of its use in agriculture as a plant fortifier promoting plant growth [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was determined that the antimicrobial and antifungal effectiveness were prominent in parallel with the increased concentrations of WV, which is thought to contribute positively to the maturation time of silage by accelerating the fermentation of organic matter in silage production. Thus, due to its high acidity and rich ethanol and phenol contents, the antibacterial and antifungal activities of WV with various concentrations have been identified many times (Koç et al, 2019;Koç et al, 2018;Rui et al, 2014). The number of lactic acid bacteria in the group treated with 2% WV decreased significantly (P<0.05) when compared to the control and the other treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…[110][111][112][113] A PA concentration of 10% significantly enhanced plant growth, fruit weight, fruit diameter and sweetness of fruits. 111 Siriwardena et al 113 PA applied to the soil improves its physical, chemical, and biological properties, providing an increase in beneficial microorganisms [116][117][118][119] and facilitating the absorption of nutrients from the soil solution by plants. 120 Koç et al 117 reported that in general the dose of PA of 3.0% ml will promoted a positive effect on the number and activity of biological factors in soil.…”
Section: Application Of Pamentioning
confidence: 99%
“…111 Siriwardena et al 113 PA applied to the soil improves its physical, chemical, and biological properties, providing an increase in beneficial microorganisms [116][117][118][119] and facilitating the absorption of nutrients from the soil solution by plants. 120 Koç et al 117 reported that in general the dose of PA of 3.0% ml will promoted a positive effect on the number and activity of biological factors in soil. According to Sun et al, 121 PA combined with biochar could reduce NH 3 volatilization in rice paddy fields.…”
Section: Application Of Pamentioning
confidence: 99%